2020
DOI: 10.1080/14616696.2020.1836384
|View full text |Cite
|
Sign up to set email alerts
|

‘I'm more afraid of racism than of the virus!’: racism awareness and resistance among Chinese migrants and their descendants in France during the Covid-19 pandemic

Abstract: This article focuses on the discrimination and racism experienced by Chinese migrants and their descendants during the Covid-19 pandemic. It analyses this group's increasing awareness and activism toward racial discrimination in French society. The paper is based on an empirical investigation using qualitative and quantitative research methods (online surveys and interviews) with people of Chinese origin living in France. In addition, qualitative data from news media and activists is also crucial to this study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
53
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 100 publications
(59 citation statements)
references
References 16 publications
2
53
0
4
Order By: Relevance
“…In particular, Chinese and other Asian migrants have been targeted due to the original emergence of the pandemic in China, with reports of bullying, awkward behaviour, avoidance of Chinese restaurants and shops, and physical attacks (82–84). In surveys and interviews with people of Chinese origin living in France, nearly a third reported having experienced at least one discriminatory act since January 2020 (85).…”
Section: Resultsmentioning
confidence: 99%
“…In particular, Chinese and other Asian migrants have been targeted due to the original emergence of the pandemic in China, with reports of bullying, awkward behaviour, avoidance of Chinese restaurants and shops, and physical attacks (82–84). In surveys and interviews with people of Chinese origin living in France, nearly a third reported having experienced at least one discriminatory act since January 2020 (85).…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, migrants with Asian, American, Turkish or former Yugoslavian backgrounds revealed larger healthrisk concerns than natives in Germany, while financial risks only appeared to rise for migrants from Turkish or former Yugoslavian backgrounds (Soiné et al 2020). During this period, discrimination became an issue for Chinese migrants and their descendants in France (Wang et al 2020a), as well as in the UK and Russia (Murji and Picker 2020). In a study of discrimination in the Belgian renting market, Verhaeghe and Ghekiere (2020) used a field-experiment approach to analyze invitations to apartment viewings of people from different ethnic groups.…”
Section: Ethnicity and Othernessmentioning
confidence: 99%
“…Thus, Tabri and colleagues [ 10 ] found that perceived existential threats stemming from COVID-19 manifested in prejudice against Chinese people in the United States. Litam and Oh [ 11 ] found that COVID-19-related racial discrimination decreased Chinese Americans’ life satisfaction via increased levels of depression (see also Wang et al [ 12 ] from France). The role of official and social media in increased prejudice has also been documented (e.g., Croucher et al, [ 13 ]).…”
Section: Introductionmentioning
confidence: 99%